Increased Degradation of Adenosine Monophosphate as a Regulator of Maximal Mitochondrial Respiration - Springer, Catherine B (East Carolina University, 2019)
Atrophied skeletal muscle have enhanced fatigability due at least in part to a reduction of mitochondria content. Mitochondrial biogenesis is regulated by the transcriptional coactivator PGC-1 alpha, which in turn is activated by AMP-activated protein kinase (AMPK). Therefore, lower levels of AMP might be expected to slow mitochondrial production and decrease mitochondrial content. Supporting this idea, the AMP degrading enzyme AMP deaminase 3 is highly induced during multiple forms of muscle atrophy, a condition that has less mitochondrial content. The purpose of this study was to determine whether an increase in the degradation of cellular AMP will result in a decrease in maximal mitochondrial oxidative capacity, an indicator of mitochondrial content. AMP degradation was increased through transduction of cultured mouse cell (C2C12) with adenoviruses encoding for enzymes that degrade AMP. Equal amounts of adenoviruses encoding for AMPD3, AMPD1, and 5'nucleotidase were administered to C2C12 myotubes for either 1 or 5 days. An adenovirus encoding for GFP was used as the negative control. Oxygen consumption rate (OCR) was assessed using a Seahorse XFe24 Analyzer and the Cell Mitochondrial Stress Test from Agilent. Oligomycin, FCCP, and a mix of antimycin A and rotenone were injected to measure basal respiration, maximal respiration, H+ leak, and ATP production. The main findings of this thesis are AMPD3 and 5'nucleotidase decreased basal maximal respiration and ATP production five days after adenovirus transduction compared to the GFP control. No significant changes were observed one days after adenovirus transduction. Surprisingly, the AMPD1 adenovirus did not produce any significant effects at either 5 or 1 days. To understand why the response to the AMPD1 adenovirus was different than the AMPD3 adenovirus, AMP deaminase enzyme activity was assessed. AMP deaminase activity was significantly higher with the AMPD1 adenovirus compared to GFP, however, compared to the AMPD3 adenovirus, AMPD activity was 96 times lower. This study supports the hypothesis that an increase in the degradation of cellular AMP leads to decreased maximal mitochondrial capacity. Since oxidative capacity is indicative of mitochondrial content, these findings suggest both AMPD3 and 5'nucleotidase decrease mitochondrial content and integrity. This defends the notion that fatigue during muscle atrophy is due, at least in part, from a decrease in mitochondrial content because of a decrease in cellular AMP.
Keywords: AMP deaminase; Mitochondrial respiration; Mitochondria--Physiology; Muscular atrophy; Adenylic acid; Musculoskeletal system